2016
DOI: 10.17077/2154-4751.1321
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone for the prevention of neonatal respiratory morbidity before elective cesarean section at term

Abstract: Background: Respiratory distress syndrome (RDS) is the principal cause of early neonatal morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
5
9
0
Order By: Relevance
“…18 On the other side many studies proved that steroids given at term prior surgical delivery were effective in reducing respiratory morbidity, neonatal sepsis and special care units admissions. 8,9,19 A large trial (ASTEC trial) found that the incidence of respiratory distress at term are reduced to the half and 6-fold decrease in the rate of NICU admission in patient given antenatal steroids. 20 Recently, many researchers requested to revisit steroids before scheduled CD based on the facts that steroids are similar to all drugs having both benefits and risks either short term or long-term risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 On the other side many studies proved that steroids given at term prior surgical delivery were effective in reducing respiratory morbidity, neonatal sepsis and special care units admissions. 8,9,19 A large trial (ASTEC trial) found that the incidence of respiratory distress at term are reduced to the half and 6-fold decrease in the rate of NICU admission in patient given antenatal steroids. 20 Recently, many researchers requested to revisit steroids before scheduled CD based on the facts that steroids are similar to all drugs having both benefits and risks either short term or long-term risks.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The benefits of steroids before scheduled CD at term are still controversial where some studies reported benefits and reduction in respiratory morbidity; other studies not recommend its use at term or even linked its use to some complications. [7][8][9][10][11][12] This study was conducted to evaluate whether dexamethasone injections at term is beneficial in reducing neonatal incubation admissions or not.…”
mentioning
confidence: 99%
“…Cesarean delivery is a known risk factor for neonatal respiratory complications, mostly transient tachypnea of the newborn (TTN) and respiratory distress syndrome (RDS) in infants at or near term. The respiratory morbidities may be severe and even fatal (1) . for the period between 37 weeks to 37 weeks and 6 days to 0.8% for the period between 39 weeks to 39 weeks and 6 days.…”
Section: Introductionmentioning
confidence: 99%
“…No serious side effects have been reported after administration of corticosteroids during pregnancy, but some studies reported a reduction in fetal body movements, fetal breathing movements and heart rate variation after betamethasone administration ( 1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is considered that whether there is a way that can effectively prevent the occurrence of lower back pain, or can effectively reduce the degree of pain. In the study of Salem et al ( 5 ), dexamethasone (DXMS) was shown to be effective in reducing adverse anesthesia during cesarean delivery. Thus whether DXMS also reduces back pain following epidural delivery analgesia is considered.…”
Section: Introductionmentioning
confidence: 99%